Interoperability of Conceptual Geographical Data Schemas using UML Infrastructure - Ferreira, Thiago Bicalho; Stempliuc, Sergio Murilo; Lisboa-Filho, Jugurta (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2016: Anais do XXXI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2016.24329, 2016)
Issues in the area of geographic databases, caused by the lack of a standard geographic conceptual data model, can be classified as interoperability problems. This paper proposes a method to reach horizontal interoperability, i.e., a schema can be transformed in another schema designed using a different model. UML infrastructure and the Enterprise Architect CASE tool are used in the process. To reduce the number of transformations between all schemas, a UML Profile called GeoProfile is used as a base model. OCL expressions are used to enforce spatial constraints.